Ubiquity of dominant cyanobacterial taxa along glacier retreat in the Antarctic Peninsula. Issue 4 (22nd March 2022) - Almela, Pablo; Casero, Cristina; Justel, Ana; Quesada, Antonio
Abstract: Cyanobacteria are key organisms in the Antarctic ecosystem, but the primary succession of its communities in recently deglaciated soils remains poorly understood. In this study, we surveyed the primary succession of cyanobacterial communities with an in-depth Next Generation Sequencing approach in three Antarctic recently glacier forefields. Despite the similar physicochemical characteristics of the soils, we did not find a common pattern in the distribution of the cyanobacterial communities at the finest level of taxonomic resolution. However, the metabarcoding analysis revealed a common community of 14 cyanobacterial identical sequences in all the studied soils, whose lineages were not restricted to polar or alpine biotopes. These ASVs comprised a relative abundance within the cyanobacterial community of 51.5%–81.7% among the three locations and were also found in two cyanobacterial mats from the Antarctic Peninsula. Our results suggest that (micro)biotic interactions act as a key driver of the community composition and dynamics of Cyanobacteria during the early stages of succession in recently deglaciated soils of Antarctica. A few common genera might play a key role in the ecosystem, due to its ubiquitous presence not only in these soils but also in microbial mats, conforming probably the most widely disperse and dominant single genotypes in Antarctic soils. Abstract : A few common genera of Cyanobacteria, not all restricted to polar regions, might play a key role in the Antarctic ecosystem, due to its ubiquitous presence in soils and microbial mats.